An insight into leadership self-efficacy among the principals of religious secondary schools in Malaysia = Satu tinjauan tentang efikasi kendiri kepimpinan dalam kalangan pengetua sekolah menengah agama di Malaysia - Hamat, Zulkefli; Mansor, Azlin Norhaini; Zaini, Abdul Razif; Sahrir, Muhammad Sabri (Core Studies Center, Selangor International Islamic University College, 2022)
This study discusses the level of leadership self-efficacy (LSE) among religious secondary school principals in Malaysia. In the context of norms in Malaysia, studies on the self -efficacy of leadership among school administrators are still lacking and limited. Thus, this study is conducted to measure the level of LSE of religious school principals involved from the aspects of (i) motivating group members, (ii) creating synergy, (iii) showing awareness and self - confidence and (iv) creating change. A mixed-method questionnaire was distributed among all 56 respondents consisting of employees of religious secondary school principals through a convenience sampling method. The self-efficacy of leadership is measured through four dimensions namely i) motivating group members, (ii) creating synergy, (iii) showing self - awareness and confidence and (iv) creating change. The results showed that the level of leadership self-efficacy for the dimension of motivating group members and creating synergy was high. However, the level of leadership self-efficacy for the dimensions of self-awareness and self-confidence as well as creating change is only at a moderately high level. Thus, to ensure that school principals have the opportunity to be selected as decision makers at the highest level of the organization, the four aspects of leadership self-efficacy must be at a high level. The findings showed that the school principals have a high level of Leadership SelfEfficacy (LSE) among themselves. They also provided additional comments and suggestions to improve the external factors that can affect their level of Leadership Self -Efficacy. It is hoped that the results of this study can provide input to the stakeholders of education in religious secondary schools on the need to hold mentoring programs or modules to help improve leadership self-efficacy (LSE) among the principals involved to achieve the transformation of 20th century education planned by the Ministry of Education, Malaysia.